Clinical Handbook of Antithrombotic : A Practical Guide - Lawrence, Anchah; Yii Ching, Wong; Pooi Yee, Chan (UNIMAS Publisher, 2021)
Antithrombotic agents are high-risk medications associated with significant rates of medication errors. The use of antithrombotic agents is extensively high in cardiology and medical specialties; thus, a good understanding of antithrombotic agents is essential. A group of pharmacists has worked collectively to come out with this handbook focusing on antithrombotic agents that are commonly established in Sarawak Heart Centre. The purpose of this handbook is to serve as reference material on antithrombotic agents for pharmacists, nurses, medical officers, medical interns, students and other healthcare providers in the medical field. Therefore, additional basic knowledge of pharmacogenetics and pharmacogenomics information of patients’ response to certain antithrombotic agents are also highlighted in this handbook. I hope the healthcare providers, trainees and students will find this handbook useful during their course of duties.